2012
DOI: 10.2478/v10102-012-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin inhibits degranulation and superoxide generation in PMA stimulated neutrophils

Abstract: Activated neutrophils represent the main source of myeloperoxidase (MPO), superoxide (SO) and subsequently derived oxygen metabolites. They have important microbicidal activities, however in inflammatory conditions they may secondarily attack surrounding tissues. Overproduction of reactive oxygen species, prolonged or excessive liberation of MPO and other effective yet also toxic substances from neutrophils may participate in disturbed apoptosis, intensify the inflammatory processes and result in serious human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…Moreover, polyphenols such as flavonoids are well known anti-inflammatory compounds and their anti-inflammatory mechanism may involve the inhibition of degranulation [ 35 , 36 ]. Other studies have reported the inhibitory effect of phenolic compounds on the neutrophil degranulation and it has been shown that flavonoids such as quercetin and rutin were potent inhibitors [ 10 , 37 ]. In addition, these two compounds were found to be present in Agelanthus dodoneifolius leaves as reported previously [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, polyphenols such as flavonoids are well known anti-inflammatory compounds and their anti-inflammatory mechanism may involve the inhibition of degranulation [ 35 , 36 ]. Other studies have reported the inhibitory effect of phenolic compounds on the neutrophil degranulation and it has been shown that flavonoids such as quercetin and rutin were potent inhibitors [ 10 , 37 ]. In addition, these two compounds were found to be present in Agelanthus dodoneifolius leaves as reported previously [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The exact mechanism(s) of action for Chrysin has not been elucidated; however, following mechanisms are proposed for flavonoids. (i) direct interaction with radicals and scavenging them as well as inhibition of xanthine oxidase activity (Nijveldt et al., ); (ii) reducing the immobilized leucocytes and degranulation of neutrophils through modulation of plasma membrane Ca +2 channels (Nijveldt et al., ; Pecivova, Macickova, Svitekova, & Nosal, ); (iii) possessing iron‐chelating and ion‐stabilizing properties which remove the causal factor of free radical development (Kumar & Pandey, ). Furthermore, Chrysin administration to adult rats has upregulated the antioxidant enzyme activity (CAT, SOD and GSH‐Px) present in sperm cell (Ciftci et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulatory, anti-inflammatory or antimicrobial properties of Hypericium species are unknown. Another example of a plant-derived compound decreasing degranulation of neutrophils is quercetin ( Kanashiro et al, 2007 ; Pečivová et al, 2012 ). Although quercetin is widespread in many plant species, in both mentioned articles quercetin was used as a synthesized compound.…”
Section: Pharmacological Modulation Of Degranulation Via Medical Plantsmentioning
confidence: 99%